Understanding the relationship between general and middle-range theorizing. Issue 3 (2nd July 2020) - Swanson, David; Goel, Lakshmi; Francisco, Kristoffer; Stock, James
Abstract : Purpose: General theories have been criticized for their inability to explore the mechanics of more specific domain knowledge and understand how, when and where general theory applies to and extends domain knowledge in supply chain management (SCM). Middle-range theorizing (MRT) is a potential solution to this limitation. This paper aims to assist researchers in understanding the relationship between MRT and general theorizing (GT) and connecting MRT research findings to general theory. Design/methodology/approach: This research provides a structured literature review of 518 articles, from eight journals in logistics, SCM and operations management. Theoretically based articles are analyzed by primary domain and SCM context. Findings: There are frameworks for conducting MRT; however, the literature does not sufficiently assist researchers in understanding how middle-range (MR) theory should relate to general theory. Findings include a better understanding of underserved areas in SCM, guideline frameworks for understanding when to apply MRT, when to apply GT and how MRT knowledge can be connected to SCM domain knowledge. Originality/value: This study provides a timely and appropriate compilation of theory research in SCM, including significant implications for both theory and practice, by helping to articulate the evolving philosophy of science in SCM.